VD_FINDINFO HC / 2021 / 78 vom 26. März 2021 - VD Tribunal cantonal (2021)
CAS CLAIR, EXPULSION DE LOCATAIRE, DÉLAI DE GARDE, CUMUL D'ACTIONS | 257d CO, 138 al. 3 let. a CPC (CH), 257 CPC (CH), 90 CPC (CH)